2017
DOI: 10.1007/s00421-017-3623-z
|View full text |Cite
|
Sign up to set email alerts
|

The presence of symptoms of testosterone deficiency in the exercise-hypogonadal male condition and the role of nutrition

Abstract: Men exhibiting EHMC do appear to present with symptoms associated with androgen deficiency. For the most part, these symptoms are limited to those reported on the AMS questionnaire, although there are also some cases of clinically low BMD. It is possible that inadequate energy intake is contributing to this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 33 publications
3
43
2
3
Order By: Relevance
“…It was reported that LEA induced through dietary restrictions resulted in significant decreases in leptin and insulin, but no changes in IGF‐1, ghrelin, testosterone, or free T 3 in recreationally active participants. Contrary to these results, evidence from cross‐sectional studies by Heikura et al and Hooper et al suggests significantly lower testosterone levels are associated with LEA (21 kcal/kg LBM/d) in both middle‐ and long‐distance runners and racewalkers. Additionally, McMurray et al reported elevations in human growth hormone (HGH) and significant decreases in IGF‐1 in wrestlers under conditions of LEA (<30 kcal/kg LBM/d).…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…It was reported that LEA induced through dietary restrictions resulted in significant decreases in leptin and insulin, but no changes in IGF‐1, ghrelin, testosterone, or free T 3 in recreationally active participants. Contrary to these results, evidence from cross‐sectional studies by Heikura et al and Hooper et al suggests significantly lower testosterone levels are associated with LEA (21 kcal/kg LBM/d) in both middle‐ and long‐distance runners and racewalkers. Additionally, McMurray et al reported elevations in human growth hormone (HGH) and significant decreases in IGF‐1 in wrestlers under conditions of LEA (<30 kcal/kg LBM/d).…”
Section: Resultsmentioning
confidence: 69%
“…Table summarizes the methods of assessing energy availability used across the cross‐sectional studies. Energy intake was measured via food frequency questionnaire or 3‐ to 7‐day food diaries using household measures or weighed records . One study measured energy intake 3 days per month .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations